Perlindungan Hukum Investor Pasar Modal Dalam Kepailitan Perusahaan Emiten - Yitawati, Krista; Sumanto, Hery (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2020)
Abstract— The capital market is an investment alternative for investors. Through the capital market, investors can invest in several companies through the purchase of securities offered. Investors will become shareholders in publicly-listed companies. The purpose of this study is about the position of capital market investors in the event of bankruptcy in the issuer's company and know the form of protection that can provide protection for capital market investors. The research method used is a normative research method by reviewing legislation. the position of capital market investors in the event of bankruptcy in the issuer's company is that the public shareholders are creditors who are included in the competitor (concurrent) while the form of legal protection needed is to maximize the functions and roles of OJK as the protectors of the issuer's stock which is accurately related to the performance and financial condition of public companies because the principle of openness is one of the rights that guarantees legal protection, and makes efforts to restructure the issuer's company to avoid bankruptcy. Keywords—: legal protection; investors; capital market; bankruptcy; issuers.